1999
DOI: 10.3181/00379727-220-44375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tea Consumption on Oxidative Stress in Smokers and Nonsmokers

Abstract: While the anticarcinogenic effects of tea in animal models have been reported by several groups, human epidemiological studies examining tea consumption and cancer prevention have produced equivocal results. The beneficial properties of tea to human health may be related to the antioxidant properties of tea components. However, little evidence has been provided that tea consumption can either increase the antioxidant capacity or decrease oxidative stress in humans. In the present study, the effects of tea trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 13 publications
2
12
1
1
Order By: Relevance
“…Others also demonstrated SOD and catalase were significantly upregulated both in vivo rat model and in smokers (1,(39)(40)(41). In this model, Chinese green tea (Lung Chen) probably arrests multiple harmful mechanisms of lung injury through protection of cells and tissues from oxidative damage by scavenging oxygen-free radicals generated from cigarette smoke exposure, in agreement with previous reports (42,43). Consequently, we observed a protection of lung morphology after 56-day CS exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Others also demonstrated SOD and catalase were significantly upregulated both in vivo rat model and in smokers (1,(39)(40)(41). In this model, Chinese green tea (Lung Chen) probably arrests multiple harmful mechanisms of lung injury through protection of cells and tissues from oxidative damage by scavenging oxygen-free radicals generated from cigarette smoke exposure, in agreement with previous reports (42,43). Consequently, we observed a protection of lung morphology after 56-day CS exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, a decrease in 8‐oxodG was observed whenever the intervention was 3 months or longer,41, 42 but not after 1 month or less 42, 43. The exception is one study in which a decrease was observed after only 7 days 44. No change in urinary 8‐oxodG was seen after 4 months of intervention with black tea 41.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical studies have found an inverse association between tea consumption and oxidative stress ( 25 27 , 50 ) . For example, by observing nineteen people in a 5-d experimental study, Stote et al ( 50 ) found that green tea consumption could lower plasma levels of F 2 -IsoP.…”
Section: Discussionmentioning
confidence: 99%